Self-Handicapping in Chinese Medical Students During the COVID-19 Pandemic: The Role of Academic Anxiety, Procrastination and Hardiness - Jia, Jun; Wang, Lin-lin; Xu, Jia-bin; Lin, Xian-hao; Zhang, Bin; Jiang, Qin (Frontiers in Psychology, 2021)
Background: In the face of the 2019 Coronavirus Disease (COVID-19) outbreak, Chinese medical students worried about their future studies, which might make them more susceptible to academic anxiety. Previous studies have shown that academic anxiety is an important risk factor for self-handicapping, but there are few studies to explore the relationship between the two which may be mediated or moderated by other variables. Therefore, this study investigated how Chinese medical students’ academic anxiety is correlated to their self-handicapping in time of COVID-19 epidemic, and explored the moderating and mediating effects of hardiness and procrastination. Methods: In this study, 320 Chinese medical students’ psychological traits were measured with Academic Anxiety Questionnaire, Self-Handicapping Scale, General Procrastination Scale and Hardiness Scale to explore the potential associations between these variables. Results: The most obvious finding from this study was that self-handicapping had a positive correlation with academic anxiety and procrastination, but had a negative correlation with hardiness; hardiness had a negative association with academic anxiety and procrastination; and academic anxiety and procrastination were positively correlated. In addition, the relationship between academic anxiety and self-handicapping of Chinese medical students was not only partially mediated by procrastination, but also moderated by hardiness. Furthermore, medical students who had lower hardiness had stronger direct effect, while the indirect effect was strong at high and low conditions of hardiness. Conclusion: In time of the COVID-19 epidemic, the academic anxiety and self-handicapping of medical students are influenced by procrastination and hardiness to a great extent. Thus, in addition to suggesting that more attention should be paid to the academic anxiety and procrastination of medical students, in the future, more attention should be paid to cultivating the hardiness of medical students and exerting its interventional role in self-handicapping.